Open Innovation 2.0 The New Mode of Digital Innovation for Prosperity and Sustainability - Curley, Martin (Innovation, Technology, and Knowledge Management, 2018)
This book presents the emerging paradigm and methodology, Open Innovation 2.0 (OI2), which aims to help drive significant structural changes and benefits through digital innovation to society and industry. It highlights how new services and markets can be co-created in open ecosystems and how this leads to a transformation from win-lose to win-win situations for all stakeholders. Organized around a number of core patterns of OI2, such as shared purpose, partnering and platforms, this book leverages more than five years of research by the EU Open Innovation Strategy Policy group. Popularized in the early 2000s, open innovation is a systematic process by which ideas can pass among organizations and travel on different exploitation vectors for value creation. With the simultaneous arrival of multiple digital disruptive technologies and rapid evolution of the discipline of innovation, it became apparent that an entirely new approach to innovation was needed that incorporated technological, societal and policy dimensions. Unlike other innovation methodologies, OI2 is an innovation paradigm and methodology with a purpose: to seek and deliver innovations that move us collectively on to a trajectory towards sustainable intelligent living. OI2 is a paradigm advocating for disruptions, seeking the unexpected and providing support for rapid scale-up of successes. As a method, it provides a safety net for both innovations and innovators, inspiring innovators to have the confidence and courage to innovate. Featuring case studies from domains such as energy, telecommunications, transportation, and finance and from companies including Intel, Lego, Alcatel Lucent and Alstom, this book is useful to industry executives, policy makers, academics, and students of innovation and innovation management.